Benzbromarone Attenuates Oxidative Stress in Angiotensin II- and Salt-Induced Hypertensive Model Rats. (5th June 2018) - Muraya, Nanako; Kadowaki, Daisuke; Miyamura, Shigeyuki; Kitamura, Kenichiro; Uchimura, Kohei; Narita, Yuki; Miyamoto, Yohei; Chuang, Victor Tuan Giam; Taguchi, Kazuaki; Maruyama, Toru; Otagiri, Masaki; Hirata, Sumio
Abstract : Oxidative stress induced by hyperuricemia is closely associated with the renin-angiotensin system, as well as the onset and progression of cardiovascular disease (CVD) and chronic kidney disease (CKD). It is therefore important to reduce oxidative stress to treat hyperuricemia. We previously found that benzbromarone, a uricosuric agent, has a direct free radical scavenging effect in vitro . The antioxidant effects of benzbromarone were evaluated in vivo via oral administration of benzbromarone for 4 weeks to model rats with angiotensin II- and salt-induced hypertension. Benzbromarone did not alter plasma uric acid levels or blood pressure but significantly reduced the levels of advanced oxidation protein products, which are oxidative stress markers. Furthermore, dihydroethidium staining of the kidney revealed a reduction in oxidative stress after benzbromarone administration. These results suggest that benzbromarone has a direct antioxidant effect in vivo and great potential to prevent CVD and CKD.